Fundamentals of Latex Film Formation Processes and Properties - Keddie, Joseph L.; Routh, Alexander F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book introduces the reader to latex, which is a colloidal dispersion of polymer particles in water, and explains how useful products are made from it. The primary focus is the process by which wet latex can be transformed into coatings, adhesives, and composites in the process known as film formation. The book reviews the main experimental techniques used to study the film formation process. It then presents the fundamental concepts for each of the three main stages of the process: evaporation of water, particle deformation, and polymer diffusion. The latest experimental observations are presented along with theoretical descriptions and models. Later chapters consider the effects of surfactant on film properties and describe films made from nanocomposite particles and from blends of latex with nanoparticles, such as clays or carbon nanotubes. The book concludes with a chapter considering the remaining technical challenges and highlighting a few exciting future directions. Throughout the presentation, fundamental concepts are emphasised. Relevant models are explained in an accessible way that does not assume prior knowledge. This book will serve as a state-of-the art reference for scientists working in industrial R&D and also for researchers in diverse academic subjects, including chemistry, physics, engineering, and materials science.
An Introduction to Latex and the Principles of Colloidal Stability -- Established and Emerging Techniques of Studying Latex Film Formation -- Drying of Latex Films -- Particle Deformation -- Molecular Diffusion Across Particle Boundaries -- Surfactant Distribution in Latex Films -- Nanocomposite Latex Films and Control of Their Properties -- Future Directions and Challenges.
Keywords: Polymers; Nanotechnology; Surfaces (Physics).; Materials Science; Surfaces and Interfaces, Thin Films; Soft and Granular Matter, Complex Fluids and Microfluidics; Polymer Sciences; Nanotechnology